Design of Booking Accounting Information System in PPTK, Cimahi Utara District - Rahayu, Ayu Sri; Gunardi, Gunardi; Abdussalam, Fallah; Trimastuti, Wahyu (Budapest International Research and Critics University, 2021)
The development of technology and science is a driving factor in the development of the world economy. This study aims to design a bookkeeping accounting information system in PPTK North Cimahi District. The research method used in the form of interviews, observations and literature review. The results of the study show several display structures on the menu, several hardware and software specifications used in the accounting information system design system. Then there are several problems encountered in the designed system, The design of the information system uses the Waterfall method using the Visual Studio 2010 programming language and the database uses Microsoft Access, so that it is expected to run as needed, and the implementation and testing of this information system can be said to have been appropriate and can run well so that it can be used to facilitate data processing. According to the needs of the institution concerned.Optimal use of accounting information systems in an institution can provide benefits to the organization, namely making it easier for organizations to adapt to a constantly changing environment, better internal control systems, and improving organizational external relations.